2007
DOI: 10.1091/mbc.e06-08-0683
|View full text |Cite
|
Sign up to set email alerts
|

Atg19 Mediates a Dual Interaction Cargo Sorting Mechanism in Selective Autophagy

Abstract: Autophagy is a catabolic membrane-trafficking mechanism conserved in all eukaryotic cells. In addition to the nonselective transport of bulk cytosol, autophagy is responsible for efficient delivery of the vacuolar enzyme Ape1 precursor (prApe1) in the budding yeast Saccharomyces cerevisiae, suggesting the presence of a prApe1 sorting machinery. Sequential interactions between Atg19-Atg11 and Atg19-Atg8 pairs are thought responsible for targeting prApe1 to the vesicle formation site, the preautophagosomal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…As expected (Farre et al, 2007), ⌬atg1 was affected in both Cvt-and autophagy-dependent maturation of Ape1, and ⌬atg11 was only impaired in the Cvt-dependent maturation of Ape1. However, in contrast to S. cerevisiae, where Atg8 is essential for the Cvt pathway and only partially required for autophagy (Kirisako et al, 1999;Abeliovich et al, 2000;Chang and Huang, 2007), PpAtg8 was essential for both processes (Supplemental Figure S4B). These results (Supplemental Figure S4, A and B) show that PpAtg8 is essential for all autophagyrelated pathways and is not redundant with Atg11 in bridging the receptor-cargo complexes with the PAS.…”
Section: Dual Interaction Of Atg30 With Atg11 and Atg17 Is Required Tmentioning
confidence: 95%
See 1 more Smart Citation
“…As expected (Farre et al, 2007), ⌬atg1 was affected in both Cvt-and autophagy-dependent maturation of Ape1, and ⌬atg11 was only impaired in the Cvt-dependent maturation of Ape1. However, in contrast to S. cerevisiae, where Atg8 is essential for the Cvt pathway and only partially required for autophagy (Kirisako et al, 1999;Abeliovich et al, 2000;Chang and Huang, 2007), PpAtg8 was essential for both processes (Supplemental Figure S4B). These results (Supplemental Figure S4, A and B) show that PpAtg8 is essential for all autophagyrelated pathways and is not redundant with Atg11 in bridging the receptor-cargo complexes with the PAS.…”
Section: Dual Interaction Of Atg30 With Atg11 and Atg17 Is Required Tmentioning
confidence: 95%
“…In growing cells Atg11 plays a major role in bridging the Ape1-Atg19 complex with the PAS. However, upon nitrogen starvation, the increased levels of Atg8 cause a partial bypass of the Atg11-dependent step (Chang and Huang, 2007). In P. pastoris Atg30 also interacts with Atg11 (Farre et al, 2008).…”
mentioning
confidence: 99%
“…Experiments in which the amount of Atg8 is clamped at levels lower than that normally generated during autophagy induction indicate that the amount of this protein correlates with the size of the autophagosome (Xie et al 2008). Atg8 that lines the concave side of the phagophore also plays a role in cargo recognition during selective types of autophagy by binding the receptors used in the Cvt pathway, pexophagy, and mitophagy (Shintani et al 2002;Chang and Huang 2007;Mijaljica et al 2012;Motley et al 2012). X-ray crystallography, combined with NMR, has revealed that a hydrophobic pocket in Atg8 interacts with the Atg8-interacting motif (AIM, or, with regard to the mammalian homolog, an LC3-interacting region, LIR) in Atg19, providing insight into the mechanism of selective cargo recognition (Noda et al 2008).…”
Section: Macroautophagymentioning
confidence: 99%
“…The C-terminal region of Atg19, which is essential for interaction with Atg8, contains hydrophobic residues homologous to that in LRS (WXXL sequence), although there is no overall sequence homology between them. 12,22,23 Atg8 might recognize Atg19 in a molecular mechanism similar to the LC3-p62 interaction.…”
Section: Other Cargo Recognition By the Atg8 Familymentioning
confidence: 99%